Between War and Peace - Feis, Herbert (Book collections on Project MUSE., 2016)
The author brings to life more clearly than ever before the moment of triumph and the intricate web of negotiations preceding the Potsdam Conference in that period between victory and cold war. His account of the Conference itself- recreating the feelings of tension, the personalities of the leaders, the steady pressures of the Russians-is likely to remain the standard reference. One sees Truman, still uncomfortable in office but determined to get matters settled quickly. There is Churchill, the master of eloquence and maneuver, suddenly replaced by Attlee in the midst of negotiations. And there is Stalin, always suspicious, always pushing for expansion. Between War and Peace shows these leaders trying to evaluate the atomic bomb, Truman hopeful Churchill enthusiastic, Stalin apparently uninterested and noncommittal. Originally published in 1960. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.